Evaluation of Eccentric Compressive Behavior Between Active and Passive Preloading in CFST - Ruyun Diao; Xiao Hu; Li Xie; Zhenlin Chen (Applied Sciences)
Concrete-filled steel tubes (CFSTs) are widely used in high-rise buildings and bridges, owing to their confinement effect on concrete. The confinement effect can enhance the compressive strength and ductility of the components. During the construction of high-rise buildings or bridges, CFST columns may be subject to an unforeseen preload known as a passive preload, which might impact a structure’s mechanical behavior. Additionally, a deliberate preload called an active preload is applied to a CFST column before application as a design strategy to improve the performance of the CFST. However, only a few studies have evaluated the effects of the two types of preloads on CFST performance. In this study, the eccentric compressive performances of passive and active preloading systems in a circular short CFST column were investigated using finite element numerical simulations. Four representative preloaded CFST columns were compared by analyzing their mechanical behaviors with two-stage loading (preloading and service loading). The influences of the eccentric ratio, concrete compressive strength, steel yield strength, and steel thickness on the load-bearing capacity ratio and M-P curves of the four preloaded CFST columns were evaluated. It was found that in comparison to passive preloaded CFSTs, the overall performance of the active column was satisfactory.